Bilingual Learning Management of Biology Lesson in Immersion Class (A Site Study at State-Owned Junior High School 5 Purworejo) - Sukiono, Bambang (2012)
This research has three aims. (1) To describe the characteristics of bilingual learning plan of biology lesson in immersion class. (2) To describe the characteristics of bilingual learning implementation of biology lesson in immersion class. (3) To describe the characteristics of bilingual learning evaluation of biology lesson in immersion class. This research is descriptive-qualitative study with ethnography approach. The informants in this study are principals, vise principal of curriculum, vice principal of facility and infrastructure, biology teacher, and the students who attend bilingual learning. Collecting the data uses interviews, observations, and documentation. The data validity was tested by triangular technique namely interviews, observations directly and indirectly. The research result involves three points. 1) Plan that had been done in bilingual learning of biology lesson in immersion class involves three kinds. (a) The arrangement of learning program such as annual program, semester program, syllabus, and lesson plan. The learning program is arranged in English. (b) The preparation and the development of human resource. (c) The preparation of facility. 2) The implementation of bilingual learning of biology lesson in immersion class was done with the integrated model. The learning used two languages (Indonesian and English) in the same time. 3) The evaluation of bilingual learning of biology lesson in immersion class involves three kinds. (a) The evaluation of learning plan. (b) The evaluation of learning implementation. (c) The evaluation of students learning result. The evaluation of plan and learning implementation was done by the principal with the assessment supervision instrument of plan and learning implementation. The evaluation of student learning result was done by the biology teacher. The evaluation of student learning result involved four kinds. 1) vocabulary test, 2) daily test (formative test), 3) mid test, and 4) final semester test (summative test).